Antibacterial nanostructured copper coatings deposited on tantalum by magnetron sputtering. (May 2015) - Wang, S.; Zhu, W.; Yu, P.; Wang, X.; He, T.; Tan, G.; Ning, C.
Abstract : Tantalum gains an increasing attention in orthopaedic and dental field due to its excellent biocompatibility. However, like other implant materials, tantalum was faced with the problem of infection. In this study, antibacterial Cu coatings with controllable content were built on tantalum via a magnetron sputtering system at varying deposition times. Field emission scanning electron microscopy, atomic force microscopy, X-ray diffraction and X-ray photoelectron spectroscopy were employed to characterise the morphologies, roughness and compositions of Cu coatings. The results indicated that the surface roughness and content of Cu coatings increased as the sputtering time. The releasing behaviour of Cu ions was further detected by atomic absorption spectrometry. Antibacterial tests showed that 90% antibacterial ratio of Cu coatings against Escherichia coli and Staphylococcus aureus were achieved when the sputtering time exceeded 1 min. The antibacterial tantalum was expected to have wider applications in orthopaedic or dental implant materials.